How to solve the DE

Dec 2015
1,084
169
Earth
\(\displaystyle y''-y =-e^{-x}\).
 
Last edited:
Dec 2015
1,084
169
Earth
My approach using Wronskian : \(\displaystyle dW(y,e^x )=-dx \; \) ; \(\displaystyle \; W(y,e^x )=C_1 -x \; \) ; \(\displaystyle \; y'e^x -e^{x} y=C_1 -x\).

\(\displaystyle y'-y=C_1 e^{-x} - xe^{-x} \; \) ; \(\displaystyle \; (ye^{-x} )'=C_1 e^{-2x} -xe^{-2x} \; \) ; \(\displaystyle \; ye^{-x} = C_2 -\dfrac{C_1 }{2} e^{-2x}+
\dfrac{\left(2x+1\right)\mathrm{e}^{-2x}}{4}

\).
\(\displaystyle y=C_2 e^{x} -\dfrac{C_1 }{2}e^{-x} +
\dfrac{\left(2x+1\right)\mathrm{e}^{-x}}{4}

\).
 

v8archie

Math Team
Dec 2013
7,712
2,682
Colombia
It's a second order linear ODE for which the homogeneous equation has the characteristic polynomial $r^2-1=0$ so the complementary solution is $y_c = c_1 e^{-x} + c_2 e^{x}$. The particular solution, by the method of undetermined coefficients, then has the form $y_p=(Ax+B)e^{-x}$.
 
  • Like
Reactions: idontknow

skipjack

Forum Staff
Dec 2006
21,479
2,470
I'll use $\text{A}$ and $\text{B}$ for the constants of integration.

Multiply by $e^{-x}$, then integrating gives $e^{-x}y' + e^{-x}y = \frac12e^{-2x} + 2\text{A}$.

Multiply by $e^{2x}$, then integrating gives $e^xy = \frac12x + \text{A}e^{2x} + \text{B}$.

Hence $y = \frac12xe^{-x} + \text{A}e^x + \text{B}e^{-x}$, which is consistent with idontknow's solution.
 
  • Like
Reactions: idontknow